2021
DOI: 10.1111/ors.12628
|View full text |Cite
|
Sign up to set email alerts
|

External root resorption in common odontogenic cysts and ameloblastomas of the jaw: A retrospective radiographic study in an Asian population

Abstract: Common odontogenic cysts and ameloblastomas of the jaw are often associated with external root resorption of adjacent teeth. Principal findingsAmeloblastomas were eight times more likely to cause root resorption than odontogenic keratocysts while dentigerous cysts were three times more likely to cause root resorption than odontogenic keratocysts. We found a clear association between the type of lesion and the presence of external root resorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…It has been reported that orthodontic forces of 50-100 cN are optimal for orthodontic tooth movement and low risk of surface resorption (Theodorou et al, 2019). Teo et al (2021) determined that the incidence of surface resorption associated with cysts was 38% in an Asian population (Teo et al, 2021). The incidence of surface resorption caused by ameloblastomas and dentigerous cysts appears to be higher than with odontokeratocysts (OKC; Struthers & Shear, 1976;Teo et al, 2021).…”
Section: Aetiology and Prevalencementioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that orthodontic forces of 50-100 cN are optimal for orthodontic tooth movement and low risk of surface resorption (Theodorou et al, 2019). Teo et al (2021) determined that the incidence of surface resorption associated with cysts was 38% in an Asian population (Teo et al, 2021). The incidence of surface resorption caused by ameloblastomas and dentigerous cysts appears to be higher than with odontokeratocysts (OKC; Struthers & Shear, 1976;Teo et al, 2021).…”
Section: Aetiology and Prevalencementioning
confidence: 99%
“…Teo et al ( 2021 ) determined that the incidence of surface resorption associated with cysts was 38% in an Asian population (Teo et al, 2021 ). The incidence of surface resorption caused by ameloblastomas and dentigerous cysts appears to be higher than with odontokeratocysts (OKC; Struthers & Shear, 1976 ; Teo et al, 2021 ).…”
Section: External Root Resorptionmentioning
confidence: 99%
See 2 more Smart Citations